Analisis Nilai Perusahaan Ditinjau Dari Corporate Social Responsibility, Tax Planning dan Aktivitas: Studi pada Perusahaan Sektor Infrastruktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 - Pandu Ramadhan; Sudarwati; Ratna Damayanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research was conducted to analyze the firm value in terms of corporate social responsibility, tax planning, and activity. this research method uses descriptive quantitative methods. The data source used is secondary data obtained from the financial statements of infrastructure companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The population in this study is infrastructure sector companies listed on the Indonesia Stock Exchange in 2021-2023, and the sample in this study obtained 11 companies and data collection using purposive sampling technique. This study uses multiple linear regression data analysis. The results showed that corporate social responsibility has no effect on firm value, tax planning has a positive and significant effect on firm value, activity has a negative and significant effect on firm value.